Review of Operation and Maintenance Methodologies for Solar Photovoltaic Microgrids - Keisang, Ketshephaone; Bader, Tobias; Samikannu, Ravi (Frontiers in Energy Research, 2021)
Global concerns and growth in electricity demand especially for rural and remote settlements have imposed governments, scientists, engineers, and researchers to look for alternative solutions in the form of renewable energy sources. High global growth in solar energy technology applications has added more weight to operations and maintenance (O&M) of solar photovoltaic (SPV) systems. SPV reliability and optimized system performance are key to ensuring success and continual adaptation of SPV technology. O&M plays a central role to warrant sustainability, long term availability throughout the operational lifetime of the elements of SPV systems whilst boosting the confidence of ultimate consumers in solar energy. While appreciating that SPV installations intrinsically require minimal maintenance actions, the objective of this manuscript is hence to reaffirm the significance of O&M scheduling in SPV systems by reviewing the O&M approaches in SPV microgrid systems. Further discussions focus on the various maintenance strategies employed in the field with special emphasis on corrective, preventive, and predictive maintenance strategies. Because of the variation in the design and development procedures of SPV systems, there is a lack of clear steps followed in the development of an O&M program for SPV systems and the evaluation of its performance. This manuscript serves to address this through a model for developing an O&M program and portrays the key elements for its success including a management and execution approach for improved risk-return balance and savings from the O&M expenditure. Eventually, the three models of executing an O&M program i.e. in-house O&M team, third party contract, or installation company are analyzed.